Ki-67 and CD100 immunohistochemical expression is associated with local recurrence and poor prognosis in soft tissue sarcomas, respectively - Campos, Marcelo (2013)
Soft tissue sarcomas (STSs) are a heterogeneous group of mesenchymal tumors of >50 subtypes. However, STSs represent <1% of types of cancer. Despite this low frequency, the disease is aggressive and treatment, when possible, is based on traditional chemotherapies. A number of cases of resistance to adjuvant therapies have been reported. Metastases are commonly identified in STS patients during diagnosis and the development of effective clinical parameters is crucial for correct management of the disease. The use of biological markers in cancer is a useful tool to determine patient prognosis. Ki-67 is a protein marker for proliferation of somatic cells and is widely used in prognostic studies of various types of tumor, including STSs. Cluster of differentiation 100 (CD100) is a member of the semaphorin family. The family was initially described as axon guidance molecules important for angiogenesis, organogenesis, apoptosis and neoplasia. CD100 was previously utilized as a prognostic factor in tumors and also in STSs. In the present study, protein expression of Ki-67 and CD100 was analyzed by immunohistochemistry in samples of STS patients of the Barretos Cancer Hospital (Barretos, Brazil) to establish prognostic criteria of the disease. Results demonstrate a correlation between CD100 expression and poor prognosis, consistent with a previous study. Moreover, the expression of Ki-67 was identified to correlate with presence of local or locoregional recurrence. To the best of our knowledge, no large casuistic study has revealed this correlation between Ki-67 and local recurrence in STSs. The use of Ki-67 and CD100 as markers in clinical pathological analysis may be suitable as a prognostic criterion in disease progression.